Communication Behavior Based on Gender Reponsive in Primary School - Ernita Arif; Aida Vitayala S Hubeis; Basita Ginting Sugihen; Ninuk Purnaningsih; Amiruddin Saleh (Institut Pertanian Bogor, 2014)
In addition to poor communication, the teacher is still differentiate between male and female students. If the communication behavior of the teacher in the learning process is not gender responsive, it will affect the successful of the learning process. Gender responsive teacher communication behavior will improve the quality of learning. The objective of this research were to analyze the communication behavior of male and female teacher in urban and rural areas. The research was conducted in the city of Padang and Padang Pariaman District began in August to December 2013. Total sample of 200 people consisting of 100 male and 100 female were scattered in cities and in villages.Data analysis using Spearman rank, Chi Sguare correlation. The research results showed that verbal communication behaviors that include snarl words, purr words, degrading words, confirmation, taboos and euphemisms including the high category is spoken by male and female the teacher in both urban and rural, communication behavior nonverbal such as tone of voice, facial expression, eye contact, proximity, and the average time high.Keywords: teacher, communication behavior, verbal and nonverbal, gender responsive